International Migration, Remittances and COVID-19: Economic Implications and Policy Options for South Asia. Issue 2 (4th May 2022) - Withers, Matt; Henderson, Sophie; Shivakoti, Richa
ABSTRACT: COVID-19 has disrupted the flow of international remittance that many South Asian economies depend upon. This 'remittance shock' is likely to catalyse a downturn in foreign exchange earnings, worsen structural unemployment and threaten the welfare of millions of low-income families. We situate the pandemic as an unprecedented challenge to the migration-development nexus in South Asia and examine the economic implications for three remittance economies: India, Nepal and Sri Lanka. We evaluate those countries' existing responses to the crisis and discuss policy alternatives, highlighting the need to recalibrate development strategies by reducing reliance on migration and remittances.